Effect of fermentation methods on physicochemical components and antioxidant activities of apple-strawberry wine - ZENG Chaozhen, MU Yuwen, YUAN Jing, SONG Juan, ZHANG Haiyan, KANG Sanjiang (Zhongguo niangzao)
Using Saccharomyces cerevisiae, Torulaspora delbrueckii, and Pichia anomala as fermentation strains, the effects of 5 different fermentation methods (single fermentation with Saccharomyces cerevisiae, co-fermentation and sequential fermentation of S. cerevisiae and non-Saccharomyces cerevisiae) on the physicochemical components and antioxidant activities of apple-strawberry wine were discussed. The results showed that the sequential fermentation method of first inoculation with S. cerevisiae and then inoculation with P. anomala 24 h later showed significant advantages in improving the efficiency of glucose metabolism, increasing the contents of organic acids, total phenols and total flavonoids, and enhancing the antioxidant capacity of fruit wine. The contents of glucose, fructose and sucrose decreased to 0.36 g/L, 75.00 g/L and 4.58 g/L, respectively, while the contents of lactic acid, citric acid and succinic acid increased to 804.87 mg/L, 2 720.45 mg/L and 560.25 mg/L, respectively. The total phenols and total flavonoids contents eventually increased to 0.95 g/L and 0.42 g/L. Ferric ion reducing/antioxidant power (FRAP), 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) free radical scavenging capacity reached 4.34 μmol Trolox/ml, 3.38 μmol Trolox/ml and 6.60 μmol Trolox/ml, respectively. The sequential fermentation of S. cerevisiae and P. anomala had significant effects on physicochemical components and antioxidant activity of apple-strawberry wine, which provided scientific basis for the production of high quality apple-strawberry wine.